2022
DOI: 10.3389/fcvm.2022.819274
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Analysis of Abnormal Lipid Indices and Hypertension for Ischemic Stroke: A 10-Year Prospective Cohort Study

Abstract: BackgroundDyslipidemia and hypertension are two important independent risk factors for ischemic stroke (IS); however, their combined effect on IS remains uncertain.ObjectivesThis present study aimed to evaluate the interaction effect of hypertension and abnormal lipid indices on IS in a 10-year prospective cohort in Chinese adults.MethodsThe cohort study of 4,128 participants was conducted in May 2009 and was followed up to July 2020. All qualified participants received a questionnaire survey, physical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
3
2
0
Order By: Relevance
“…The pathophysiological mechanism by which lipids may have a role in hypertension development is not fully clear. It could be partly explained by the evidence that dyslipidemia triggers endothelial injury, and the loss of physiological vasomotor activity which induced by endothelial injury may become presented as increased blood pressure 49,50 . Our study showed that the mean levels of triglyceride, total cholesterol, and LDL‐C were significantly higher in the hypertensive group, which is consistent with the results of previous studies 51 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The pathophysiological mechanism by which lipids may have a role in hypertension development is not fully clear. It could be partly explained by the evidence that dyslipidemia triggers endothelial injury, and the loss of physiological vasomotor activity which induced by endothelial injury may become presented as increased blood pressure 49,50 . Our study showed that the mean levels of triglyceride, total cholesterol, and LDL‐C were significantly higher in the hypertensive group, which is consistent with the results of previous studies 51 .…”
Section: Discussionsupporting
confidence: 91%
“…It could be partly explained by the evidence that dyslipidemia triggers endothelial injury, and the loss of physiological vasomotor activity which induced by endothelial injury may become presented as increased blood pressure. 49,50 Our study showed that the mean levels of triglyceride, total cholesterol, and LDL-C were significantly higher in the hypertensive group, which is consistent with the results of previous studies. 51 We found that the mean level of HDL-C was not statistically different between hypertensive and non-hypertensive groups.…”
Section: Variablesupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found that the highest risk of CVD was in individuals with both high non-HDL-C and high baPWV, and that this was 1.89 times higher than in individuals with both normal non-HDL-C concentration and baPWV. Although the present study is the first to demonstrate the combined effect of non-HDL-C and baPWV on the risk of CVD, similar analyses ( 32 – 34 ) of the combined effects of lipids and blood pressure on CVD risk have been performed previously. Yang et al ( 34 ) showed that individuals with both hypertension and hypercholesterolemia are at a higher risk of CVD than those with hypertension or hypercholesterolemia alone in a study of 5,092 participants who were followed for 20.84 years.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, Sánchez-Íñigo et al (24) evidenced that triglycerides-related variables had the advantage to evaluate the risk of developing hypertension in the Spanish population. Wei et al (25) found that a high concentration of lipid ratios worked synergistically with hypertension to affect the incidence of ischemic stroke. A lot of research pointed out that TG/HDL-C was favorable to identify increased urinary albuminto-creatinine ratio, insulin resistance, diabetes risk, incident hypertension, and cardiovascular events (26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%